Exploring adherence to an early rule-out pathway for myocardial infarction in the emergency department using mixed-methods. (3rd October 2022) - Ferry, A V; Wereski, R; Marshall, L; Strachan, F E; Schulberg, S D; Bularga, A; Chapman, A R; Lee, K K; Anand, A; Mills, N L
Abstract: Background: Incorporating a high-sensitivity cardiac troponin assay into a care pathway for the assessment of suspected acute coronary syndrome has enabled myocardial infarction to be ruled out earlier. Purpose: Using mixed methods, we explored adherence to an early rule-out pathway in the HiSTORIC (High-Sensitivity Cardiac Troponin on Presentation to Rule Out Myocardial Infarction) randomised controlled trial. Methods: In 16, 972 consecutive patients we evaluated clinician adherence to an early rule-out pathway for the assessment of suspected acute coronary syndrome. Adherence was defined in patients with presentation cardiac troponin I concentrations <5ng/L and symptom onset >2 hours from presentation without serial troponin testing (type 1 adherence); presentation troponin <5ng/L and symptom onset ≤2 hours from presentation with serial testing (type 2 adherence); or presentation troponin between 5ng/L and sex-specific 99th centile with serial testing (type 3 adherence). Semi-structured interviews were conducted with 23 clinicians to aid interpretation of the quantitative analysis. Qualitative data were coded and organized into themes. Results: In patients with troponin <5ng/L presenting >2hr from symptom onset, adherence was achieved in 81% of patients. In patients presenting ≤2hr from symptom onset, 35% of patients had a second troponin test. In patients with an initial troponin concentration between 5ng/L and the 99th centile, 65% of patients had a second troponin test. Compared to patients managed by clinicians who were adherent to the pathway, patients with troponin over-testing (type 1 non-adherence) were more likely to be older (mean age 52±16 years versus 58±14, P<0.001) and have a history of coronary disease (11% versus 27%, P<0.001). In contrast, patients with under testing (type 2 non-adherence) tended to be younger (mean age 49±16 versus 63±15, P<0.001), female (50% versus 37%, P<0.001) and have lower presentation troponin levels (median concentration 1.0ng/L IQR 1.0 to 2.0, versus 5.0ng/L IQR 2.0–10.0) compared to those in whom testing was performed according to pathway recommendations. Semi-structured interview data revealed how pathway adherence was influenced by five main themes: guideline characteristics, patient characteristics, the healthcare practitioner, the healthcare system and scientific evidence. Clear visual pathway layout was fundamental in achieving optimal adherence. Strong clinical suspicion of acute coronary syndrome promoted repeat troponin testing and deviation from the pathway was felt to be justifiable by more senior clinicians. Conclusion: This analysis revealed successful implementation of the early rule-out pathway with interview data aiding interpretation of trial data. Younger patients with lower troponin concentrations were less likely to receive pathway recommended serial troponin testing. Clinical judgement is one of the main reasons for discontinuation of pathway recommendations. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation